Simultaneous T1 and T2 measurements using inversion recovery TrueFISP with principle component-based reconstruction, off-resonance correction, and multicomponent analysis - Pfister, Julian; Bartsch, Andreas J.; Breuer, Felix A. (Magnetic resonance in medicine, 2019)
Purpose: To improve the reconstruction quality for quantitative T1 and T2 measurements using the inversion recovery (IR) TrueFISP sequence and to demonstrate the potential for multicomponent analysis. Methods: The iterative reconstruction method takes advantage of the high redundancy in the smooth exponential signals using principle component analysis (PCA). Multicomponent information is preserved and allows voxel-by-voxel computation of relaxation time spectra with an inverse Laplace transform. Off-resonance effects are analytically and numerically investigated and a correction approach is presented. Results: Single-shot IR TrueFISP in vivo measurements on healthy volunteers demonstrate the improved reconstruction performance compared to a view sharing (k-space weighted image contrast [KWIC]) reconstruction. Especially, tissue components with short apparent relaxation times T1* are not filtered out and can be identified in the relaxation time spectra. These components include myelin in the human brain (T1* ≈ 130 ms) and extra cranial subcutaneous fat. Conclusion The PCA-based reconstruction method improves the temporal accuracy and preserves multicomponent information. Spatially resolved relaxation time spectra can be obtained and allow the identification of tissue types with short, apparent relaxation times.
Im Titel ist bei "T1" die 1 und bei "T2" die 2 tiefgestellt
Gesehen am 22.10.2019